Thioredoxin h2 and o1 Show Different Subcellular Localizations and Redox-Active Functions, and Are Extrachloroplastic Factors Influencing Photosynthetic Performance in Fluctuating Light - Liang-Yu Hou; Martin Lehmann; Peter Geigenberger (MDPI AG, 2021)
Arabidopsis contains eight different h-type thioredoxins (Trx) being distributed in different cell organelles. Although Trx h2 is deemed to be confined to mitochondria, its subcellular localization and function are discussed controversially. Here, cell fractionation studies were used to clarify this question, showing Trx h2 protein to be exclusively localized in microsomes rather than mitochondria. Furthermore, Arabidopsis trxo1, trxh2 and trxo1h2 mutants were analyzed to compare the role of Trx h2 with mitochondrial Trx o1. Under medium light, trxo1 and trxo1h2 showed impaired growth, while trxh2 was similar to wild type. In line with this, trxo1 and trxo1h2 clustered differently from wild type with respect to nocturnal metabolite profiles, revealing a decrease in ascorbate and glutathione redox states. Under fluctuating light, these genotypic differences were attenuated. Instead, the trxo1h2 double mutant showed an improved NADPH redox balance, compared to wild type, accompanied by increased photosynthetic efficiency, specifically in the high-light phases. Conclusively, Trx h2 and Trx o1 are differentially localized in microsomes and mitochondria, respectively, which is associated with different redox-active functions and effects on plant growth in constant light, while there is a joint role of both Trxs in regulating NADPH redox balance and photosynthetic performance in fluctuating light.